Dopamine Alters AMPA Receptor Synaptic Expression and Subunit Composition in Dopamine Neurons of the Ventral Tegmental Area Cultured with Prefrontal Cortex Neurons - Gao, Can (J Neurosci, 2007)
Excitatory synapses onto dopamine (DA) neurons of the ventral tegmental area (VTA) represent a critical site of psychostimulant-induced synaptic plasticity. This plasticity involves alterations in synaptic strength through AMPA receptor (AMPAR) redistribution. Here, we report an in vitro model for studying regulation of AMPAR trafficking in DA neurons under control conditions and after elevation of DA levels, mimicking cocaine exposure. We used cocultures containing rat VTA neurons and prefrontal cortex (PFC) neurons from enhanced cyan fluorescent protein-expressing mice. In VTA-PFC cocultures, D(1) receptor activation (10 min) increased synaptic and nonsynaptic glutamate receptor subunit 1 (GluR1) and GluR2 surface expression on DA neurons. NMDA or AMPA receptor antagonists blocked this effect, and it was not observed in pure VTA cultures, suggesting that DA agonists acted on D(1) receptors on PFC neurons, altering their excitatory transmission onto VTA DA neurons and, thus, influencing AMPARs. To mimic the longer elevation in extracellular DA levels produced by systemic cocaine, cocultures were incubated with DA for 1 h. Synaptic GluR1 was increased 24 h later, reminiscent of the increased AMPA/NMDA ratio at excitatory synapses onto VTA DA neurons 24 h after cocaine injection (Ungless et al., 2001). In contrast, GluR2 was unchanged. Analysis of colocalization of surface GluR1–3 labeling suggested that control DA neurons express a substantial number of GluR1/2, GluR2/3, and homomeric GluR1 receptors and that the increase in surface AMPARs 24 h after DA exposure may in part reflect increased GluR1/3-containing receptors. These results help define the cellular basis for plasticity underlying the development of behavioral sensitization.